PENGARUH MODEL PEMBELAJARAN LEARNING STARTS WITH A QUESTION MENGGUNAKAN MEDIA VISUAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP - Fitriana Rahmawati; Nurashri Partasiwi (Epsilon: Jurnal Pendidikan Matematika, 2021)
The learning starts with a questions learning model is one way that stimulates students to ask questions without any explanation of the material from the teacher first. The purpose of this study was to determine the effect of the learning starts with a questions learning model on students' mathematical communication skills in learning mathematics. The method used in this research is the experimental method. The population in this study were all eighth grade students of SMP Perintis 1 Bandar Lampung which were divided into 2 classes with a total of 50 students. The sample was taken using total random sampling, which consisted of 2 classes, namely the experimental class VIIIa who learned to apply the learning starts with a questions learning model and the control class VIIIb who learned to use conventional learning. Data collection techniques using test techniques. Data analysis was used using t test. Based on the results of data analysis, it was found that thit = 5.03, and from the distribution table at a significant level of 5%, it was obtained that tdaf = 2.02. The result reminds that thit thit > tdaf. The results showed that the average experimental class learning outcomes = 81.56 while the control class learning outcomes = 63.68, that thit >tdaf. From the results of research and data analysis, it can be concluded that the learning starts with a questions learning model has a positive effect on the mathematical communication skills of class VIII odd semester students of SMP Perintis 1 Bandar Lampung in the 2020/2021 academic year.